Patterson D. M. Dworkin on the Semantics of Legal and Political Concepts / trans. from Engl. A. B. Didikin, S. A. Aleksandrov - A. B. Didikin; S. A. Aleksandrov (Омский научный вестник: Серия "Общество. История. Современность")
In a recent comment on H. L. A. Hart’s «Postscript» to The Concept of Law, Ronald Dworkin claims that the meaning of legal and political concepts maybe understood by analogy to the meaning of natural kind concepts like «tiger», «gold» and «water». This article questions the efficacy of Dworkin’s claims by challenging the use of natural kinds as the basis for a semantic theory of legal and political concepts. Additionally, in matters of value there is no methodological equivalent to the scientific method. Thus, there is little hope of finding hidden essences to explain the meaning of legal and political concepts. Finally, even if there are natural kinds, Dworkin’s arguments for their efficacy in jurisprudence are problematic and unpersuasive. The problem for Dworkin is that his embrace of natural kinds undermines the «fit» side of the fit/justification model of adjudication that lies at the heart of his theory of law